A novel oral immunotherapy strategy using transgenic barley induces Culicoides allergen-specific immune responses in horses - von der Höden, Fenja Johanna; Stefansdottir, Sara Björk; Torsteinsdottir, Sigurbjörg; Svansson, Vilhjalmur; Björnsson, Jon Mar; Wagner, Bettina; Mahmuti, Dorontina; Marti, Eliane; Jonsdottir, Sigridur (Frontiers in Immunology, 2026)
IntroductionInsect bite hypersensitivity (IBH) is a seasonal, IgE-mediated allergic dermatitis of horses caused by salivary gland proteins of biting midges (Culicoides spp.). Current management relies on relief of clinical signs and on physical protection. In a previous pilot study, healthy horses were fed transgenic barley expressing a Culicoides allergen via a special spiral bit, which successfully induced allergen-specific antibody responses. Building on this concept, the present study aimed to evaluate a more practical feeding approach, delivering transgenic barley expressing the major Culicoides allergen Cul o 2p in a feed-compatible paste administered from buckets.MethodsTwelve naïve Icelandic horses were randomized into treatment (n=6) and control (n=6) groups. The treatment group received 11.44 g of the major Culicoides allergen Cul o 2p/horse across three feeding phases. Serum and saliva were analyzed for Cul o 2p-specific antibodies (IgG1, IgG4/7, IgG5, IgA, IgE) by ELISA. IgE-blocking capacity was assessed in pooled serum, and cytokine responses (IL-10, IL-4, IFN-γ) measured after in vitro re-stimulation of peripheral blood mononuclear cells (PBMCs).ResultsFour of six treated horses produced Cul o 2p-specific IgG1, IgG4/7, and IgA in both serum and saliva. The induced antibodies could partly inhibit IgE binding. Elevated secretion of IFN-γ and IL-10 but no IL-4 secretion was observed in supernatants of re-stimulated PBMCs in treated horses compared to controls, reaching statistical significance for IFN-γ. No Cul o 2p-specific IgE was detected, and no adverse clinical reactions occurred during treatment.ConclusionThe feed-based approach using transgenic barley paste induced Cul o 2p-specific humoral and cellular immune responses in naïve horses, supporting its potential as a scalable and field-feasible platform for prophylactic and therapeutic applications in IBH. Clinical trials in IBH-affected horses are warranted to assess efficacy.